2015
DOI: 10.1007/s10792-015-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness and intraocular pressure in premature infants

Abstract: To evaluate the central corneal thickness (CCT) and intraocular pressure (IOP) of premature infants and to document correlation of them with gestational age, chronological age, and birth weight of infants. Using a hand-held applanation tonometer and a portable pachymeter, IOP and CCT of 170 premature infants were measured just before initial retinopathy of prematurity screening examination and re-measured 4 weeks after the first visit. The CCT and IOP were positively correlated during the first (r = 0.616, p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[5] However, Karahan et al [8] found that CCT did not correlate with gestational age or birth weight in their cross-sectional study. The CCT in Sekeroglu et al [13] was negatively correlated with gestational age and birth weight. Ng et al [24] was the only other study that found strong negative association between IOP and postconceptive age, head circumference, body weight, and body length.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[5] However, Karahan et al [8] found that CCT did not correlate with gestational age or birth weight in their cross-sectional study. The CCT in Sekeroglu et al [13] was negatively correlated with gestational age and birth weight. Ng et al [24] was the only other study that found strong negative association between IOP and postconceptive age, head circumference, body weight, and body length.…”
Section: Discussionmentioning
confidence: 98%
“…We found a similar trend for each individual infant over the course of this study. To date, 6 longitudinal studies [3,7,13,16,19] have reported a range of mean values (Table 1). These differences may reflect the differences in racial groups as well as the mean gestational age of the infants in different cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…13 Other research teams did longitudinal studies of IOP in premature newborns to follow its changes with their maturation. 2,[16][17][18][19][20][21] All of the studies showed a statistically significant (p<0.01) decline of IOP values with a negative correlation between the postconceptual age and birth weight of the infants. Only Choo et al did not find a statistically significant difference in IOP between premature and full-term newborns.…”
Section: Screeningmentioning
confidence: 90%
“…Sekeroglu et al were the first team to do a longitudinal study and track both values of IOP and CCT at different postconceptual ages in the same infant. 18 Their results showed a positive correlation between CCT and IOP. Acar and colleagues later became the other team to show similar results.…”
Section: Screeningmentioning
confidence: 92%
“…Few studies have addressed corneal thickness and its determinants in children in recent years 4, 5, 6, 7. These studies have shown that congenital diseases, race and ethnicity, body mass index, nutritional status, gestational age at birth, refractive errors, and corneal curvature radius are the most important determinants of central and paracentral corneal thicknesses 4, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%